A agência McCann-Erickson do Brasil: um estudo sobre a profissionalização do campo publicitário brasileiro (1935-1964) - Lopes, Patrícia Sunah de Negreiros (2016)
The theme of this dissertation is professionalization in advertising. Specifically in Brazilian advertising, and taking into account that professionalization in this field was articulated with the expansion and consolidation of the biggest North American publicity agencies in Latin America between the 1930s and 1960s, this research focuses on analyzing the contribution of the North American publicity agency McCann-Erickson in developing the advertising field. Assuming the hypothesis that there is a particularity in the Brazilian experience of McCann, this research demonstrates how the sociology of professions, added to the theory of construction of fields, can be applied to study of the consolidation of publicity as a unique professional community. This research also demonstrates how the historical contexts of creation of the Brazilian and the North American advertising fields intertwine with the trajectory of the agency McCann-Erickson in Brazil. Finally, this research also analyzes the mechanisms and the specific capitals operated by this agency in order to assert its dominant position in the Brazilian advertising field.